Technological system of production and consumption of biogas - Чайковська, Євгенія Євстафіївна (Eastern-European Journal of Enterprise Technologies, 2014)
Known optimization methods of cogeneration systems using biogas based on static evaluation of process parameters are not always able to ensure the maintenance of the ratio of production of heat and electricity in difficult conditions of mismatch of their consumption and unstable output of biogas, which requires additional equipment due to additional volumes of gas-holders and complication of thermal schemes. For resource and energy saving, it was proposed to maintain a ratio of production and consumption of electricity and heat based on the technological system, which is based on the integrated dynamic subsystem, including a biogas plant, heat pump, cogeneration unit, storage battery and electric thermal accumulator. Based on the resulting information, obtained as a result of performance monitoring and state identification of a biogas plant, systems evaporator-compressor, compressor-condenser of the heat pump and performance monitoring and state identification of electric accumulators and electric heat accumulators using mathematical models of the dynamics of the biogas plant, evaporator, compressor, condenser of the heat pump of the electric accumulator and electric thermal accumulator, a method for integrated decision-making in conditions of mismatch of energy production and consumption was developed. Based on forecasting the changes in process parameters of production and consumption of biogas it is possible to make proactive decisions to maintain the fermentation process, which allows timely unloading of fermented raw and loading of fresh material. In conditions of ensuring the constant biogas yield and the absence of expenditure of generated heat for maintaining the fermentation process, it is possible to accumulate generated electricity not only for the operation of the heat pump compressor, but also in the hours of its wasteful production. This approach allows to increase the marketability of the biogas plant and reduce the cost of electricity production to (10-15) %. Biogas saving, for example, during fermentation of 60.2 t/day of raw material is 49.4 m3/year, which gives an annual reduction of carbon dioxide emission by 75.6 tons/year. Moreover, waste of anaerobic fermentation can be used not only as a low-grade energy source for the heat pump, but also as a fertilizer, corresponding to environmental protection conditions.